Testing extreme-axion wave-like dark matter using the BOSS Lyman-alpha forest data. Issue 3 (28th January 2019) - Leong, Ka-Hou; Schive, Hsi-Yu; Zhang, Ui-Han; Chiueh, Tzihong
Abstract: Using cosmological particle hydrodynamical simulations and uniform ultraviolet backgrounds, we compare Lyman-α forest flux spectra predicted by the conventional cold dark matter (CDM) model, the free-particle wave dark matter (FPψDM) model, and extreme-axion wave dark matter (EAψDM) models of different initial axion field angles but with a fixed boson mass m b  ∼ 10 −22 eV against the BOSS Lyman-α forest absorption spectrum. We recover results reported previously that the CDM model agrees better with the BOSS data than the FPψDM model by a large margin, and we find that the difference of total χ 2 's is 120 for 420 data bins. These previous results demand a larger boson mass by a factor >10 to be consistent with the date and are in tension with the favoured value determined from local satellite galaxies. We however find that such tension is alleviated as some EAψDM models predict Lyman-α flux spectra agreeing better with the BOSS data than the CDM model, and the difference of total χ 2 's can be as large as 24 for the same bin number. We stress that our results are obtained based on optimization of a limited set of parameters with others fixed to a well-known heating model as priors; hence, the results are not fully optimized and should be taken as a strong indicator.